Improved Performance Evaluation For Line Of Mass Production Using Firefly Algorithm - Talal Yassin, Alla (Opción, 2019)
Assembly planning of line mass production is a process which determine the reliable sequence of assembling products. The use of simulation in line mass production planning can reduce the cost of products industries with the help of CAE computer aided engineering programs. The aim of the present study is to develop a computational model able to enhance a mass production system. The firefly algorithm is used to find the optimum solution for product assem- bly processes. It generates the simulation information by using specific Monti Carol method using assembly line recognizer. The recognizer as a contribution in this research developed based on real data belong to general company for electrical Industries in Iraq/ Baghdad/ waziriya. The generated data organ- ized by evolutionary algorithm based on the priority of station sequence and the distances between them. The simulation results provide an enhancement in the time of production due to the reduction of line processes.